Relevance and evaluation of the benchmark dose in toxicology - Baralić, Katarina; Javorac, Dragana; Antonijević , Evica; Buha Djordjevic, Aleksandra; Ćurčić, Marijana; Đukić-Ćosić , Danijela; Bulat, Zorica; Antonijević , Biljana (Archives of Pharmacy, 2020)
This paper aims to present the importance of the benchmark dose (BMD) as a point of departure (the lowest dose or concentration in the experiment that deviates from the response that differs from the normal response) in toxicological risk assessment, as well as to present commonly used software for its calculation (BMDS and PROAST). Benchmark dose is defined as a statistical lower confidence limit of a dose that results in a small change in effect (5-10%) in comparison with the control value. The BMD approach is considered a substitution for the NOAEL approach, which uses the highest observed no-effect level (NOAEL) to obtain the reference dose. The BMD approach is a methodically more forward-thinking technique than the NOAEL approach because it has statistical power and provides a wide range of dose-response relationships and allows the determination of their uncertainty and variability. Moreover, the BMD approach contributes to the reduction of experimental animals in toxicity studies. Therefore, the European Food Safety Authority (EFSA) recommends the use of BMDL10 values ​​for quantal and BMDL05 for continuous data.
Keywords: toxicology; risk assessment; benchmark dose; PROAST; BMDS